Slanting the Holocaust in the Fairy Tale Form: Jean-Claude Grumberg’s The Most Precious of Cargoes - Kristin Rozzell Murray (Humanities)
This article analyzes Jean-Claude Grumberg’s 2019 Holocaust fairy tale, The Most Precious of Cargoes, translated from French. This fairy tale adds to Grumberg’s oeuvre of Holocaust fiction, including plays and children’s stories. His fairy tale may be his most personal attempt to process his own Holocaust experience, as he includes an appendix with facts about his father and grandfather who died in Auschwitz. Specifically, the fairy tale is approached through an analysis of the fairy tale genre’s pairing with the subject of the Holocaust. The article also examines possible readings of such a pairing through a close reading of the tale that analyzes the role of good vs. evil. Published interviews with Grumberg, theory on the fairy tale, and other Holocaust fairy tales establish a view that The Most Precious of Cargoes is unique in Holocaust fiction.